Replacing “parachute science” with “global science” in ecology and conservation biology - Asase, A; Mzumara‐Gawa, TI; Owino, JO; Peterson, AT; Saupe, EE (Wiley, 2021)
Biodiversity remains relatively unknown and understudied in many parts of the developing world with significant information gaps, in stark contrast to many areas in the developed world, where knowledge about biodiversity can approach encyclopedic. Access to resources, such as funding, data, information, expertise, and biological collections (often collected by colonial-era scientists from across the developing world), is often quite limited for developing-world scientists. The life of a biodiversity scientist in the developing world is therefore one of manifold dilemmas and challenges, as well as numerous opportunities. Although collaborations exist between developing-world scientists and developed-world scientists, too many of those collaborations are not deep or permanent, and developing-world scientists are too often relegated to a subordinate role. The focus in this contribution is on providing suggestions for how to open and build access to resources for developing-world scientists. Everyone benefits if developing-world and developed-world scientists work together collaboratively to pose interesting and novel questions, generate new data, update existing data, carry out analyses, and arrive at interesting insights and interpretations. In this way, the biodiversity science community can replace “parachute” science with “global science.”